Pengelolaan Keuangan Desa dalam Mewujudkan Good Financial Governance di Desa Lembang - Widuri Wulandari; Siti Munawaroh; Agustina Setiawan (PERSPEKTIF, 2023)
This paper aims to analyze village financial management in realizing good financial governance in Lembang Village. The problem of tension is on the village's ability to properly and correctly manage village finances. There are still many villages that are wrong in implementing village financial management. Lembang Village is a village in West Bandung Regency and is the only one with the status of an independent village. This research method is qualitative. Data collection techniques by interviews, observation, and documentation. Data analysis by collecting data, reducing data, presenting data, and drawing conclusions. This study concluded that village financial management carried out by the Village Financial Management Technical Executor (PTPKD) in Lembang Village was good. From the planning to reporting and accountability stages, everyone plays a role and works together. Every stage in financial management, starting from planning, implementing, administering, reporting and accountability has been carried out by the principles of financial management, namely transparency, accountability, participatory and orderly and disciplined budgeting. By carrying out all the existing principles, the Lembang Village Government by the Development Village Index (IDM) that Lembang Village has the status of an independent village, and also the Lembang Village Government has implemented good financial governance.